Improving maternal, infant and young child nutrition in Nepal via peer mobilization. Issue 4 (6th November 2017) - Singh, Akriti; Klemm, Rolf DW; Mundy, Gary; Pandey Rana, Pooja; Pun, Bhim; Cunningham, Kenda
Abstract: Objective: To evaluate the impact of a peer facilitator (PF) approach for improving mothers' knowledge and practices relating to maternal and child nutrition. Design: A quasi-experimental design nested within a large-scale integrated nutrition programme, Suaahara, in Nepal. Suaahara interventions were implemented in all study sites, but peer facilitators were used in only half of the study sites. Setting: Rural, disadvantaged villages in three districts of Nepal: Bhojpur, Bajhang and Rupandehi. Subjects: Mothers of children aged 6–23·9 months ( n 1890). Results: Differences over time between comparison (C) and intervention (I) groups show that the PF approach had a significant positive impact on several indicators of mothers' knowledge and practices relating to maternal and child nutrition: (i) knowing that fruits and vegetables are good for children 6–23·9 months (C: −0·7, I: 10·6; P =0·03); (ii) child dietary diversity (C: 0·02, I: 0·04; P =0·02); (iii) child minimum dietary diversity (≥4 of 7 food groups; (C: 6·9, I: 16·0; P =0·02); (iv) maternal dietary diversity (C: 0·1, I: 0·4; P =0·01); and (v) maternal minimum dietary diversity (≥4 food groups; C: 3·6, I: 14·0; P =0·03). Additionally, exposure to a PF three or more times in the past 6 months was positively associated with a small improvement in maternal ( β =0·06, P =0·04) and child ( β =0·06, P =0·02) dietary diversity scores. Improvements were not observed in maternal health-seeking behaviours such as number of antenatal care visits. Conclusions: Peer mobilization is a potential approach for improving health- and nutrition-related knowledge and behaviours among women in hard-to-reach communities of Nepal.